Gender inequality and burden of orofacial clefts in the Eastern Mediterranean region: findings from global burden of disease study 1990-2019 - Sara Sadat Nabavizadeh; Jennifer J. Mootz; Nasser Nadjmi; Benjamin B. Massenburg; Kaveh Khoshnood; Ehsan Shojaeefard; Hossein Molavi Vardanjani (BMC, 2024)
Abstract Background Gender inequality may be associated with the burden of orofacial clefts (OFCs), particularly in low-and middle-income countries (LMICs). To investigate the OFCs' burden and its association with gender inequality in the Eastern Mediterranean region (EMR). Methods Country-specific data on the OFCs' prevalence and Disability-Adjusted Life Years (DALYs) from 1990 to 2019 were gathered from the Global Burden of Disease database by age and gender. Estimated annual percentage change (EAPCs) was used to investigate the OFCs' trends. The association of the Gender Inequality Index (GII) with prevalence and DALY rates was determined using multiple linear regression. Human Development Index (HDI), Socio-Demographic Index (SDI), and Gross Domestic Product (GDP) were also considered as potential confounders. Results In 2019, the overall regional OFCs' prevalence and DALYs (per 100,000 person-years) were 93.84 and 9.68, respectively. During the 1990-2019 period, there was a decrease in prevalence (EAPC = -0.05%), demonstrating a consistent trend across genders. Moreover, within the same timeframe, DALYs also declined (EAPC = -2.10%), with a more pronounced reduction observed among females. Gender differences were observed in age-specific prevalence rates (p-value = 0.015). GII was associated with DALYs (βmale= -0.42, p-value = 0.1; βfemale = 0.48, p-value = 0.036) and prevalence (βmale= -1.86, p-value < 0.001, βfemale= -2.07, p-value < 0.001). Conclusions Despite a declining prevalence, the burden of OFCs remained notably significant in the EMR. Gender inequality is associated with the burden of OFCs in the Eastern Mediterranean region. Countries in the region should establish comprehensive public policies to mitigate gender inequalities in healthcare services available for OFCs.